ANALYSIS OF RESIDENTIAL RESERVOIR CAPACITY AT THE MUTIARA PURI HARMONI 2 CIKARANG - Imamuddin, Mohammad; Prasetyo, Adi Tathak Wahyu (Universitas Ibn Khaldun Bogor, 2021)
Cikarang is one of the areas in the administrative city of Bekasi Regency, which has several flood-prone areas. Every year, several areas of Cikarang often experience flooding, including the North Cikarang area. Precisely in Karanganyar Village, Karang Bahagia Subdistrict, where most of the land has been converted from rice fields to densely populated housing. Over time, Karang Bahagia Subdistrict became familiar with floods and puddles. Mutiara Puri Harmoni 2 Housing is one of the densely populated residential areas in the Karang Bahagia District. From the observation of the drainage system made by Mutiara Puri Harmoni 2 Housing, there is a lot of sedimentation and some of the sections have a lot of narrowing due to increased development in the housing area. For the drainage before it is drained into the nearest river, namely the Gemboro river, the Mutiara Puri Harmoni 2 housing drainage system creates a reservoir as a storage. By analyzing the reservoir section using the rainfall distribution method and the Log Pearson III method, the resulting 2-year rainfall intensity is 74.374 mm/hour with the resulting discharge of 3.339 m3/second. From the calculation results, the reservoir storage is 6057.216 m3/second with a cross section of 62.4 mx 55.62m. Taking into account the reservoir water balance using 17 years of rainfall data, the maximum discharge in February is 18323m3 and the lowest discharge is in August of 3038m3. Therefore, the results of the capacity analysis needed to avoid flooding are to deepen and expand the reservoir and/or add a pump so that the concentration time is not too long.